Preliminary results on growing second generation biofuel crop miscanthus X Giganteus at the polluted military site in Ukraine - Pidlisnyuk, V.; Trögl, J.; Stefanovska, T.; Shapoval, P.; Erickson, Larry E. (My University, 2020)
The semi-field research on using second-generation biofuel crop Miscanthus x giganteus for restoration of former military site in Kamenetz-Podilsky, Ukraine was carried out during two vegetation seasons. Despite high metal pollution of soil, in particular, by Fe, Mn, Ti, and Zr, no growth inhibition was observed. The concentrations followed pattern soil > roots > stems > leaves. Accumulation of particular metals in roots was different: Fe, Mn and Ti were accumulated rather palpably after the first vegetation season and less tangible after the second one. Cu, Pb and Zn were less accumulative in both vegetation seasons, and for As and Pb the accumulative concentrations were very small. Accumulations in the aboveground parts of the plant in comparison to roots were significantly lower in case of Fe, Ti, Mn, Cu, Zn, Sr and even statistically comparable to zero in case of As, Pb and Zr. Calculated translocation ratio of metals in the plant's parts preferably indicated lack of metals' hyper accumulation. Generally, no correlations were observed between concentrations of metals in the soil and in the upper plant's parts. The research confirmed the ability of Miscanthus x giganteus to grow on the military soils predominantly contaminated by metals. © by Josef Trögl 2016.
Citation: Pidlisnyuk, V., Trögl, J., Stefanovska, T., Shapoval, P., & Erickson, L. (2016). Preliminary results on growing second generation biofuel crop miscanthus X Giganteus at the polluted military site in Ukraine. Nova Biotechnologica et Chimica, 15(1), 77-84. doi:10.1515/nbec-2016-0008
Keywords: Miscanthus X Giganteus; Phytotechnology; Restoration Of Military Contaminated Soil; Translocation Ratio